Sustainability Report, Eco-Efficiency, dan Nilai Perusahaan pada Industri Perbankan dan Keuangan di Indonesia - Priscia Sintia; Lauren Angelie; Nathalie Hizkia; Shabrina Afifah Rosy (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Institut Bisnis dan Informatika Kwik Kian Gie, 2025)
This study aims to analyze the effect of Sustainability Report disclosure on firm value in the banking and financial industry in Indonesia and to examine the role of eco-efficiency as an additional factor influencing firm value. The background of this study is based on the increasing corporate awareness of sustainability as well as growing demands from regulators and stakeholders. This study employs a descriptive approach grounded in Stakeholder Theory and Legitimacy Theory. The results indicate that the disclosure of Sustainability Reports has a positive effect on firm value, particularly in large companies that receive greater market attention. However, the impact of sustainability reporting becomes stronger when companies also implement eco-efficiency practices, such as energy efficiency, paper reduction through digital banking, and green financing initiatives. The integration of sustainability reporting and eco-efficiency practices not only enhances economic performance but also strengthens social legitimacy and competitive advantage in the banking and financial sector in Indonesia.